Box breathing or six breaths per minute: Which strategy improves athletes post-HIIT cardiovascular recovery? - Murat Kasap; Gökhan Recep Aydin (PLoS ONE, 2025)
Post-exercise recovery strategies are critical for athletic performance, yet the acute effects of controlled breathing techniques (box breathing vs. 6 bpm [6 breaths/min]) following high-intensity interval training (HIIT) remain understudied. This study compared three breathing protocols’ impact on cardiovascular and perceptual recovery metrics. In a randomized crossover design, 40 physically active university students (25 males, 15 females; age 20.95 ± 1.75 years) completed three HIIT sessions on a spin bike (15 min, 1:2 work: rest ratio at 85–95% HRmax). One of three recovery breathing protocols was applied during each session: Spontaneous breathing (control), Box breathing (4-4-4-4), 6 bpm (5–5). Heart rate (HR) was monitored continuously, and perceived exertion was assessed via Borg Scale (6–20). Data were analyzed using repeated-measures ANOVA and Tukey’s HSD post-hoc tests (α = 0.05). Box breathing elicited significantly: Higher post-exercise HR (164.65 ± 9.40 bpm) vs. 6 bpm (154.77 ± 12.18 bpm; p < 0.001*, Cohen’s d = 0.907*) and spontaneous breathing (159.05 ± 10.38 bpm; p = 0.054*), Elevated perceived exertion (Borg 17.27 ± 1.30) vs. 6 bpm (15.25 ± 1.08; p < 0.001*) and spontaneous breathing (15.25 ± 1.35; p < 0.001*). No significant difference in recovery time was observed (p = 0.128*), though box breathing showed a trend toward delayed HR baseline recovery (753.02 ± 150.60 sec vs. 675.70 ± 157.24 sec with 6 bpm). While 6 bpm appears optimal for post-HIIT recovery, box breathing may impose physiological and perceptual stress. Practitioners should tailor breathing strategies to individual tolerance and exercise intensity. These findings highlight the need for personalized recovery protocols in athletic training.